LedPred: an R/bioconductor package to predict regulatory sequences using support vector machines - Seyres, Denis; Herrmann, Carl (Bioinformatics, 2016)
Abstract. Summary: Supervised classification based on support vector machines (SVMs) has successfully been used for the prediction of cis-regulatory modules (CRMs)
Advance access publication date: 1 December 2015
Gesehen am 13.05.2020